2012
DOI: 10.1590/s0034-737x2012000600015
|View full text |Cite
|
Sign up to set email alerts
|

Initial performance of maize in response to NPK fertilization combined with Herbaspirillum seropedicae

Abstract: RESUMO Desempenho inicial do milho, em resposta à adubação NPK combinada com a inoculação de Herbaspirillum seropedicaeA inoculação de bactérias promotoras de crescimento de plantas pode ser uma abordagem tecnológica útil para aumentar a produção de milho. O objetivo deste trabalho foi avaliar o desempenho inicial de plantas de milho, em resposta à aplicação de doses de NPK combinadas com a inoculação da bactéria diazotrófica Herbaspirillum seropedicae, em experimento em casa de vegetação. A matriz experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
3
9
0
1
Order By: Relevance
“…The positive effect of increasing NPK fertilization on NPK uptake is mainly explained by the effect of NPK fertilizers on grain and stover yields as mentioned before in Table 2, where nutrient uptake was calculated by multiplying grains and stover yield by nutrient concentration (Ismail et al, 2006). These results are in accordance with those obtained by Baldotto et al (2012) and Hassanien (2018).…”
Section: Nutrients Statussupporting
confidence: 94%
“…The positive effect of increasing NPK fertilization on NPK uptake is mainly explained by the effect of NPK fertilizers on grain and stover yields as mentioned before in Table 2, where nutrient uptake was calculated by multiplying grains and stover yield by nutrient concentration (Ismail et al, 2006). These results are in accordance with those obtained by Baldotto et al (2012) and Hassanien (2018).…”
Section: Nutrients Statussupporting
confidence: 94%
“…IAA is a molecule that is synthesized by plants and a few microbes (Basse et al, 1996). These results are in agreement with those obtained by Baldotto et al (2012) who found that with increasing rates of fertilizers, there was a decrease in the root / shoot ratio, confirming the increased availability of nutrients in the root environment. Also, Pavlíková et al (2012) showed that N is a macronutrient present in many key biological molecules and it is available for plants predominantly as NO 3…”
Section: Maize Plant Distributionssupporting
confidence: 90%
“…As in the case of our study, PSB increased plant biomass but the activities of PSB towards P-solubilization in P-deficient soils could be different to different plant species and the prevailing environmental conditions [57,58]. One more phenomenon, i.e., production of organic acids by PSBs, enhances the P-mobilization/solubilization [59] in the sandy soil and finally enables the plant to uptake mineral nutrients [60]. In addition, the carboxylic groups of the acids increase the chelation of the cations, which further bind to phosphate and convert them into soluble forms [61,62].…”
Section: Discussionsupporting
confidence: 49%